Organizational Support Mediation in Employee Performance among Educational Staff: Mediasi Dukungan Organisasi dalam Kinerja Pegawai Kependidikan - Karunia, Ignatius Tri Putra; Djawoto, Djawoto; Suhermin, Suhermin (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Educational staff are central to higher education quality and academic service sustainability. Specific Background Low compliance with working hours, reflected in an average absence rate of 6.68% among 90 educational staff, indicates challenges in discipline, responsibility, and employee performance. Knowledge Gap Prior findings on self-esteem and self-efficacy in employee performance remain varied, while organizational support as a mediating mechanism requires empirical clarification. Aims This study examined self-esteem and self-efficacy in relation to employee performance, with organizational support positioned as a mediating variable. Results SEM PLS analysis showed that self-esteem was significantly related to organizational support (p = 0.003) but not directly related to employee performance (p = 0.169). Self-efficacy was significantly related to organizational support (p = 0.000) and employee performance (p = 0.029). Organizational support was significantly related to employee performance (p = 0.000) and mediated the relationships between self-esteem, self-efficacy, and employee performance. The model explained 60.9% of employee performance variance, and all constructs met validity and reliability criteria. Novelty This study positions organizational support as a central mechanism connecting internal self-beliefs with work outcomes among educational staff. Implications Higher education management should align psychological capacity development with supportive organizational systems, including appreciation, feedback, fair procedures, and adequate work resources, to strengthen employee performance and academic service quality. Highlights• Self Esteem showed a significant pathway to institutional backing but not to work outcomes.• Self Efficacy showed significant direct pathways to institutional backing and work outcomes.• SEM PLS explained 60.9% of variance with valid and reliable constructs. KeywordsSelf Esteem; Self Efficacy; Organizational Support; Employee Performance; Educational Staff